EFFECT OF INCREASING THE MIXTURE OF SAGO FLOUR AND JACKFRUIT SEED FLOUR ON CONSUMER ACCEPTANCE AND THE QUALITY OF CATFISH BALLS (Pangasius hypophthalmus) - Desi Nawati Boru Manurung; N.Ira Sari; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe purpose of this study was to determine the effect of increasing the mixture of sago flour and jackfruit seed flour as well as the nutritional value of catfishballs. The experimental method was used in this study that was doing a processing of catfish balls with an increased mixof sago flour and jackfruit seed flour. The design used was a non-factorial Completely Randomized Design (CRD) with four treatment levels, namely B1 (T 60%: TS 20%: TBN 20%), B2 (T40%: TS 30% g: TBN 30%), B3 (T 20%: TS 40%: TBN 40%), B4 (TS 50%: TBN 50%). Based on resultthat catfish ballswith 40% tapioca flour, 30% sago flour and 30% jackfruit seed flour (B2 treatment) was most preferable by consumer acceptance with 63 panelists (78.75%). The results of parameters tested about catfish balls with an increased in the mixture of sago flour and jackfruit seed flour significantly affected the organoleptic value at 95% of confidence level with value of appearance 7.47 (rather creamy), aroma 7.52 (aroma jackfruit began to smell), taste 7.45 (typical of catfish balls and jackfruit taste were increasingly felt) and texture 7.47 (chewy); with moisture, protein, fat, ash, crude fiber, carbohydrate content, and Total Plate Countwas 19.48%, 25.58%, 16.51%, 3.44%, 2.11%, 32.88%, and 2.1x103 cells/gram, respectively. Keywords:fishball,catfish, sago flour, jackfruit seed flour